Fostering Civic Knowledge in Students with Special Needs: Approaches and Strategies for Inclusive Education - Diana Puspitaningrum; Sutrisno Sutrisno; Sunarto Sutrisno; Afiah Nur Fadilah (AL-ISHLAH: Jurnal Pendidikan, 2025)
While the education system traditionally prioritizes Civic Knowledge for all students, it often overlooks the specific needs of students with special needs. Ensuring that these students acquire adequate Civic Knowledge is crucial for their development as responsible citizens. This qualitative research adopts a case study approach at the Jenangan Ponorogo State Special Needs School. Purposive sampling was used to select the principal and the teacher responsible for Pancasila education as key informants. Data were collected through interviews, observations, and documentation to capture in-depth insights. The study identifies three main approaches to implementing Civic Knowledge for students with special needs: (1) a harmony-based approach, emphasizing mutual respect and collaboration; (2) a discipline-based approach, focusing on structured behavior and consistency; and (3) an Indonesian-based approach, incorporating national values and cultural identity. Additionally, four key strategies were found to be effective: (1) habituation of worship, fostering spiritual growth; (2) cultivation of philanthropic values, encouraging empathy and social responsibility; (3) democratic practice, promoting active participation; and (4) promotion of good citizenship, reinforcing civic duties. The integration of these three approaches and four strategies offers a comprehensive framework to enhance Civic Knowledge among students with special needs. Tailoring Civic Education in this manner not only supports their civic competence but also promotes inclusivity and active citizenship. These findings contribute valuable insights for educators and policymakers aiming to develop effective Civic Knowledge programs for special needs education.